GmIDD Is Induced by Short Days in Soybean and May Accelerate Flowering When Overexpressed in Arabidopsis via Inhibiting AGAMOUS-LIKE 18 - Yang, Xue; Zhang, Yuntong; Shan, Jinming; Sun, Jingzhe; Li, Dongmei; Zhang, Xiaoming; Li, Wenbin; Zhao, Lin (Frontiers in Plant Science, 2021)
Photoperiod is one of the main climatic factors that determine flowering time and yield. Some members of the INDETERMINATE DOMAIN (IDD) transcription factor family have been reported to be involved in regulation of flowering time in Arabidopsis, maize, and rice. In this study, the domain analysis showed that GmIDD had a typical ID domain and was a member of the soybean IDD transcription factor family. Quantitative real-time PCR analysis showed that GmIDD was induced by short day conditions in leaves and regulated by circadian clock. Under long day conditions, transgenic Arabidopsis overexpressing GmIDD flowered earlier than wild-type, and idd mutants flowered later, while the overexpression of GmIDD rescued the late-flowering phenotype of idd mutants. Chromatin immunoprecipitation sequencing assays of GmIDD binding sites in GmIDD-ox Arabidopsis further identified potential direct targets, including a transcription factor, AGAMOUS-like 18 (AGL18). GmIDD might inhibit the transcriptional activity of flower repressor AGL18 by binding to the TTTTGGTCC motif of AGL18 promoter. Furthermore, the results also showed that GmIDD overexpression increased the transcription levels of flowering time related genes FLOWERING LOCUS T (FT), SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1), LEAFY (LFY) and APETALA1 (AP1) in Arabidopsis. Taken together, GmIDD appeared to inhibit the transcriptional activity of AGL18 and induced the expression of FT gene to promote Arabidopsis flowering. These results demonstrated that GmIDD might participate in photoperiodic signal transduction pathways in soybean.